Assessing Alternative Specimens for Toxicological Analysis: A Review (Indian Internet Journal of Forensic Medicine and Toxicology, 2024)
The use of alternative matrices in toxicological analyses has increased in forensic  toxicological analysis. Alternative samples to blood, visceral organs, and urine are  useful for reliability and comprehensiveness regarding generating toxicological  profiles. The article critically reviews recent literature on alternative matrices like  oral fluid, hair, skeletal tissue, sweat, cerebrospinal fluid, meconium, breast milk,  and vitreous humor and their applications in forensic toxicology. It analyzes the  characteristics, advantages, limitations, and applications of alternative matrices in  drug and poison analysis. This review article further discusses the characteristics  of biological matrices used in forensic analyses as substitutes for whole blood,  urine, and viscera samples. Each matrix type has advantages regarding sampling,  preservation, extraction methods, detection time frame, drug levels, and other  factors. However, these matrices also have limitations, such as limited drug  incorporation, correlation with concentrations for effects, low xenobiotic levels,  and the need for proper sample preparation and analysis. Although there is data  on detecting traditional drugs of abuse in alternative matrices, information on the  detection of emerging illicit drugs in these matrices is scarcer. Alternative biological  specimens play a crucial role in forensic toxicology, but they come with distinct  limitations and characteristics that must be considered. The results from analyzing  these samples may differ based on the type of specimen. Alternative matrices will  remain a focus in forensic toxicology due to their benefits and potential use when  blood, urine, or visceral organs are inaccessible or impractical, particularly in cases  like drug-facilitated sexual assault, burnt bodies, or decomposed remains.
Keywords: Alternative specimens; forensic toxicology; skeletal tissue; vitreous humor; drug-facilitated sexual assault